Business information needs and seeking behavior of tie and dye Small and Medium scale Entrepreneurs (SMSEs) - Peter, Siyao; Mosha, Goodluck E.; Ochieng, Lucy Mathoro. (Journal Article in Interdisciplinary Studies on Information Technology and Business (ISITB, 2024)
A research paper submitted to the Journal Article in Interdisciplinary Studies on Information Technology and Business (ISITB